Jantung, Medan magnet, Kesehatan KORELASI MASSA TUBUH TERHADAP DETAK JANTUNG PADA MENCIT BALB-C YANG DIPAPAR MEDAN MAGNET EXTREMELY LOW FREQUENCY (ELF) INTENSITAS 100 µT - Siti Hindun Hindiyati (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2023)
Exposure to an Extremely Low Frequency (ELF) magnetic field with an intensity of 100 µT has been set as a threshold value for health effects, but it still needs to be studied for its biological impact, especially on the function of the heart organ. This study aims to examine "The Correlation of Body Mass to Heart Rate of Balb-C Mice Exposed to an Extremely Low Frequency (ELF) Magnetic Field of 100 µT Intensity". This study used a True Design Experiment with a completely randomized design (CRD), by subjecting Balb/C mice to an ELF magnetic field intensity of 100 µT intermittently for 2 hours/day for 15 days and 30 days. A sample of 21 Balb/c mice was divided into 3 groups, the control group, and 2 groups exposed to an ELF magnetic field of 100 µT intermittently 2 hours/day for 15 days and 30 days. The variables measured in this study were body weight and heart rate per second. Weight measurements were carried out using a digital balance with an accuracy of 0.00gr with 3 measurements accompanied by 3 observers while heart rate measurements were carried out by manually counting using the human senses assisted by using a stopwatch as a timer for 5 minutes each. The data from this study were analyzed using correlation statistical analysis using SPSS 23 software. The results showed that the ELF magnetic field intensity of 100 µT on the 30th day had higher body mass and heart rate than the control group. This is because the intensity of 100 µT causes excessive muscle work in the hearts of Balb-C mice